2016
DOI: 10.1021/acs.joc.5b02375
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Duplex Thermodynamic Stability and Enhanced Nuclease Resistance of 5′-C-Methyl Pyrimidine-Modified Oligonucleotides

Abstract: Although judicious use of chemical modifications has contributed to the success of nucleic acid therapeutics, poor systemic stability remains a major hurdle. The introduction of functional groups around the phosphate backbone can enhance the nuclease resistance of oligonucleotides (ONs). Here, we report the synthesis of enantiomerically pure (R)- and (S)-5'-C-methyl (C5'-Me) substituted nucleosides and their incorporation into ONs. These modifications generally resulted in a decrease in thermal stability of ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 68 publications
5
48
0
Order By: Relevance
“…This simple combination of backbone and sugar modification provides additional resistance to exonucleases—the primary effectors of RNA degradation—and an order of magnitude increase in oligonucleotide accumulation in vivo . Methylation of the 5′ carbon to give ( S )-5′- C -methyl-RNA 93 has also been used to enhance 3′-exonuclease resistance.…”
Section: Chemical Evolution Of Sirnasmentioning
confidence: 99%
“…This simple combination of backbone and sugar modification provides additional resistance to exonucleases—the primary effectors of RNA degradation—and an order of magnitude increase in oligonucleotide accumulation in vivo . Methylation of the 5′ carbon to give ( S )-5′- C -methyl-RNA 93 has also been used to enhance 3′-exonuclease resistance.…”
Section: Chemical Evolution Of Sirnasmentioning
confidence: 99%
“…Compared to the successful ribose 2′-position modifications mentioned above, modifications at the C4′ and C5′ positions of ribose have been explored in less detail. Recently we examined a series of chirally pure ( R )- and ( S )-5′- C -methyl pyrimidine modifications and found that they affect thermodynamic stability negatively and in a manner that depends on the configuration at C5′ ( 15 ). In regard to protection against nucleases, the ( S )-epimers with various 2′-substituents were more effective than the corresponding ( R )-epimers.…”
Section: Introductionmentioning
confidence: 99%
“…Their widespread applications span from therapeutic agents, such as antibacterial [ 3 5 ], antiviral [ 6 ] or antitumor [ 7 – 8 ] drugs, to epigenetic modulators [ 9 ] or chemical tools [ 10 11 ]. Furthermore, they represent central monomers for oligonucleos(t)ide synthesis [ 12 17 ]. In the past decades, chemical modifications of these crucial building blocks have been extensively studied, both on the nucleobase itself and on the sugar moiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It can also be created directly on the nucleoside, either by functionalization of an alkene at C-5’ [ 27 32 ] or by the diastereoselective addition of a nucleophile on a carbonyl group. The latter can involve either the reduction of a ketone at C-5’ [ 12 , 33 35 ], or the addition on an aldehyde of various nucleophiles such as enolates [ 15 , 36 38 ], allylborane [ 39 ], dialkyl phosphites [ 40 ], TMSCN [ 41 ] or Grignard reagents [ 12 , 17 , 35 , 42 47 ]. Aside from the use of chiral ligands promoting an excellent facial discrimination of the aldehyde [ 34 ], the addition of Grignard reagents usually proceed with moderate diastereoselectivity and yield ( Table 1 ) [ 12 , 35 , 43 46 48 ].…”
Section: Introductionmentioning
confidence: 99%